Redefining User Involvement in Digital News Media. (2nd January 2018) - Krumsvik, Arne H.
Abstract : This article provides insight into the strategic priority of various approaches towards user involvement and how these are changing over time. A longitudinal series of surveys studying prioritizations among editorial staff identify a redefinition of user involvement in digital media: from 2012 to 2015 the role of users has been reframed from co-producers to distributors. This indicates that promotion and business development gain prominence at the expense of the traditional focus on user participation to ensure media's social role. At the same time, the approaches increasing in importance are those least likely to challenge the traditional understanding of journalists' professional role.